2021
DOI: 10.1073/pnas.2023752118
|View full text |Cite
|
Sign up to set email alerts
|

Fever supports CD8 + effector T cell responses by promoting mitochondrial translation

Abstract: Fever can provide a survival advantage during infection. Metabolic processes are sensitive to environmental conditions, but the effect of fever on T cell metabolism is not well characterized. We show that in activated CD8+ T cells, exposure to febrile temperature (39 °C) augmented metabolic activity and T cell effector functions, despite having a limited effect on proliferation or activation marker expression. Transcriptional profiling revealed an up-regulation of mitochondrial pathways, which was consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…The first approach embraces in vitro preconditioning of cells with metabolic modulators before adoptive transfer. Examples include inhibiting Akt function to favor a more Tm cell–like metabolic phenotype in mouse melanoma models ( 59 ); using sodium bicarbonate to reverse the lactic acid–induced interference with T cell glycolysis and cytotoxic function in mouse models and patients with acute myeloid leukemia ( 110 ); and transiently exposing donor lymphocytes to 39°C prior to infusion in a myeloid leukemia mouse model ( 158 ). Similarly, preconditioning T cells with IL-15, which drives Tm cell differentiation and metabolically increases spare respiratory capacity ( 66 ), has similar positive results in HER2-positive tumors, leukemia, and glioma models ( 159 161 ).…”
Section: Overcoming Metabolic Competition In the Tumor Microenvironment To Improve Tm Cellsmentioning
confidence: 99%
“…The first approach embraces in vitro preconditioning of cells with metabolic modulators before adoptive transfer. Examples include inhibiting Akt function to favor a more Tm cell–like metabolic phenotype in mouse melanoma models ( 59 ); using sodium bicarbonate to reverse the lactic acid–induced interference with T cell glycolysis and cytotoxic function in mouse models and patients with acute myeloid leukemia ( 110 ); and transiently exposing donor lymphocytes to 39°C prior to infusion in a myeloid leukemia mouse model ( 158 ). Similarly, preconditioning T cells with IL-15, which drives Tm cell differentiation and metabolically increases spare respiratory capacity ( 66 ), has similar positive results in HER2-positive tumors, leukemia, and glioma models ( 159 161 ).…”
Section: Overcoming Metabolic Competition In the Tumor Microenvironment To Improve Tm Cellsmentioning
confidence: 99%
“…Specifically, we discovered a loss of KLF and ETS:RUNX activity in T EX , while an intense heat shock signature was dominating both cytotoxic and dysfunctional TILs, suggesting that heat shock responses exert additive chromatin remodelling to other T cell states. In light of the sustained positive effect of heat 50 on tumor control by T cells this observation merits further investigation of the underlying molecular mechanisms of heat shock proteins on T cell gene-regulatory cues. Further, our analysis suggests an involvement of different nuclear receptors and octamer transcription factors in shaping T cell dysfunction in the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, daily mild heat treatment (40°C, 0.5 h/day) is sufficient to maintain low levels of both WT and P323L mutant of NSP12 (Figures 1(n) and 1(o) , compare lanes 3, 4 to 1), suggesting clinical potential of heat treatment against both WT and P323L mutation harboring SARS-CoV-2 variants. In addition, it is demonstrated that mild heat treatment upregulates the immune function [ 16 , 17 ], which might contribute to inhibition of SARS-CoV-2 fitness as well. Comorbidities such as chronic diseases and acute organ injuries are strongly correlated with disease severity and mortality among COVID-19 patients [ 18 ].…”
Section: Main Textmentioning
confidence: 99%